1983
DOI: 10.1128/jcm.17.1.149-154.1983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genital herpes simplex infections by a tissue culture-fluorescent-antibody technique with biotin-avidin

Abstract: Several cell lines were evaluated for their suitability for rapid detection of herpes simplex virus (HSV) from clinical genital specimens. Human foreskin fibroblast (Flow 7000) cells were found to be most suitable in terms of sensitivity and adherence characteristics. HSV in clinical specimens was isolated by a standard tissue culture method by monitoring the cytopathic effect, and the titers of the HSV-positive specimens were determined. More than 65% of the HSV-positive genital specimens showed titers of les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The tissue culture method is generally considered standard, but it requires up to 7 days for completion. We have reported that short-term tissue culture followed by staining is as sensitive as and more rapid (24 h) than tissue culture alone (12,13). Direct staining of tissue smears is rapid, but not as sensitive or specific as tissue culture (13), and electron microscopy is rapid, but less available and less sensitive than tissue culture (9).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The tissue culture method is generally considered standard, but it requires up to 7 days for completion. We have reported that short-term tissue culture followed by staining is as sensitive as and more rapid (24 h) than tissue culture alone (12,13). Direct staining of tissue smears is rapid, but not as sensitive or specific as tissue culture (13), and electron microscopy is rapid, but less available and less sensitive than tissue culture (9).…”
mentioning
confidence: 97%
“…Some of the methods currently available to detect HSV include conventional tissue culture techniques (15), shortterm tissue culture followed by staining (12,13) or electron microscopy (9), and direct staining of tissue smears taken from the lesions of the patient (3,7,17,18). The tissue culture method is generally considered standard, but it requires up to 7 days for completion.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Protein A and protein G, derived from the cell wall of Staphylococcus aureus and certain streptococci, respectively, bind certain IgG subclasses from various species and thus can sometimes be substituted for species-specific secondary antibodies (DeLellis, 1981;Hrapchak, 1980;Mahoney and Chernesky, 1999). Other popular modifications of the indirect method that amplify signal by increasing the concentration of enzyme bound to the solid phase are the peroxidaseantiperoxidase (PAP) and avidin-biotin-enzyme complex (ABC) techniques (Hsu et al, 1980;Milios and Leong, 1988;Nerurkar et al, 1982). The ABC system makes use of the strong interaction between avidin, an egg-white protein, or streptavidin from Streptomyces avidinii, and the low-molecular-weight vitamin biotin coupled to antibodies and enzymes (Wilchek and Bayer, 1984).…”
Section: 240mentioning
confidence: 99%